The Content of the Education of Future Music Teachers in Ukraine and the Prc on the Principles of Integration - Yang, Zhang (Journal of Danubian Studies and Research, 2023)
The article provides a comparative analysis of the training of future music teachers in the modern conditions of standardization of the content of school art education in Ukraine and the People’s Republic of China, the leading role of the integrated principle of education in the modern conditions of standardization of education in Ukraine and the People’s Republic of China is determined, the main elements of the content of the education of future music teachers based on the principles of integration are outlined, the main stages of its formation are defined; the main methods of implementing the content of education are proposed (showing, artistic practice, execution of sketches, sketching of an artistic work, variable development of artistic material, demonstration of artistic works, artistic illustration, etc.); the pedagogical conditions for improving the implementation of the content of the education of future music teachers based on the principles of integration were revealed.